The Akt signaling pathway contributes to postconditioning’s protection against stroke; the protection is associated with the MAPK and PKC pathways - Gao, Xuwen; Zhang, Hanfeng; Takahashi, Tetsuya; Hsieh, Jason; Liao, Janette; Steinberg, Gary K.; Zhao, Heng (Journal of neurochemistry, 2008)
We previously reported that ischemic postconditioning with a series of mechanical interruptions of reperfusion reduced infarct volume 2 days after focal ischemia in rats. Here, we extend this data by examining long‐term protection and exploring underlying mechanisms involving the Akt, mitogen‐activated protein kinase (MAPK) and protein kinase C (PKC) signaling pathways. Post‐conditioning reduced infarct and improved behavioral function assessed 30 days after stroke. Additionally, postconditioning increased levels of phosphorylated Akt (Ser473) as measured by western blot and Akt activity as measured by an in vitro kinase assay. Inhibiting Akt activity by a phosphoinositide 3‐kinase inhibitor, LY294002, enlarged infarct in postconditioned rats. Postconditioning did not affect protein levels of phosphorylated‐phosphatase and tensin homologue deleted on chromosome 10 or ‐phosphoinositide‐dependent protein kinase‐1 (molecules upstream of Akt) but did inhibit an increase in phosphorylated‐glycogen synthase kinase 3β, an Akt effector. In addition, postconditioning blocked β‐catenin phosphorylation subsequent to glycogen synthase kinase, but had no effect on total or non‐phosphorylated active β‐catenin protein levels. Furthermore, postconditioning inhibited increases in the amount of phosphorylated‐c‐Jun N‐terminal kinase and extracellular signal‐regulated kinase 1/2 in the MAPK pathway. Finally, postconditioning blocked death‐promoting δPKC cleavage and attenuated reduction in phosphorylation of survival‐promoting εPKC. In conclusion, our data suggest that postconditioning provides long‐term protection against stroke in rats. Additionally, we found that Akt activity contributes to postconditioning’s protection; furthermore, increases in εPKC activity, a survival‐promoting pathway, and reductions in MAPK and δPKC activity; two putative death‐promoting pathways correlate with postconditioning’s protection.